Wide Area Oscillation Damping using Utility-Scale PV Power Plants Capabilities - Mehrdad Moradi; Pouria Maghouli (Institute of Advanced Engineering and Science, 2017)
With increasing implementation of Wide Area Measurement Systems (WAMS) in power grids, application of wide area damping controllers (WADCs) to damp power system oscillations is of interest. On the other hand it is well known that rapidly increasing integration of renewable energy sources into the grid can dangerously reduce the inertia of the system and degrade the stability of power systems. This paper aimed to design a novel WADC for a utility-scale PV solar farm to damp out inter area oscillations while the main focus of the work is to eliminate the impact of communication delays of wide-area signals from the WAMS. Moreover the PV farm impact on inter area oscillation mitigation is investigated in various case studies, namely, with WADC on the active power control loop and with WADC on the reactive power control loop. The Quantum Particle Swarm Optimization (QPSO) technique is applied to normalize and optimize the parameters of WADC for inter-area oscillations damping and continuous compensation of time-varying latencies. The proposed method is prosperously applied in a 16-bus six-machine test system and various case studies are conducted to demonstrate the potential of the proposed structure.